Decentering health research networks: Framing collaboration in the context of narrative incompatibility and regional geo-politics. (January 2022) - Waring, Justin; Crompton, Amanda; Overton, Charlotte; Roe, Bridget
Research innovations and breakthroughs are increasingly realised through collaborative networks amongst state and non-state actors. This article investigates the utilisation of such networks in the field of applied health services research, where policy narratives repeatedly emphasise the importance of collaboration between university researchers, clinical and health service leaders, patient representatives and industry. The translation of policy into practice suggests that these networks are not always designed and managed in line with policy aspirations. Taking a decentred approach, the study reported in this article examines how local policy actors translate national policies for collaborative health research networks in the context of their own histories of applied research, including local narratives and priorities for health research. The study shows that local actors face key dilemmas and opportunities for situated agency, as they experience three competing policy narratives, first, for carrying out world-class research; second, for ensuring research meets local needs and third, for developing new understanding about the implementation of research into practice. Although these expectations might appear coherent to policy-makers, at the regional level, they provide the basis for disagreement and negotiation amongst local policy actors through which the local narrative of collaborative research is framed to regional stakeholders. The study shows how the tensions between elite and local narratives can be reconciled through re-framing activities, especially the articulation of 'parallel frames' within a 'cascade framing' process.